The Influence of Annealing Temperature and Holding Time Near Glass Transition Temperature on the Tensile Strength of Fused Deposition Modeling Printed Polylactic Acid - Michael Evan; The Jaya Suteja; Sunardi Tjandra (Politeknik Negeri Lhokseumawe, 2023)
Thermal annealing can be implemented to improve the mechanical strength of a 3D printing object. The critical parameters of thermal annealing are temperature and holding time. Based on the literature review, the implemented annealing temperature affects the required holding time. As the use of a lower annealing temperature and holding time can reduce the required heat and increase the process efficiency, this research investigates the implementation of the annealing temperature near glass transition temperature with a short holding time. The aim of this research is to investigate the influence of the thermal annealing temperature range from 65 °C to 85 °C and the holding time from 45 minutes to 75 minutes on the Ultimate Tensile Strength of a Polylactic Acid part printed by using Fused Deposition Modelling. The experiment implemented a 32-factorial design methodology with two replications. The experiment results indicate that the thermal annealing slightly exceeding glass transition temperature facilitates higher interlayer diffusion of raster and layers and consequently increases the Ultimate Tensile Strength. Meanwhile, the holding time does not influence the Ultimate Tensile Strength of the annealed part as the holding time range cannot accomplish the maximum crystallization for the annealing temperature range between 65 °C to 85 °C.